A floating aquatic system employing water hyacinth for municipal landfill leachate treatment: effect of leachate characteristics on the plant growth. Issue 4 (1st July 2005) - El-Gendy, A S; Biswas, N; Bewtra, J K
Abstract : The current research demonstrates the effects of certain parameters, usually present in municipal landfill leachate, on the growth of water hyacinth ( Eichhornia crassipes ), a floating aquatic plant, when used for treatment of leachate. Experiments were carried out to investigate the ability of water hyacinth to grow in leachate with different salinity ions concentrations, nutrients, pH, and heavy metals concentrations. The ability of water hyacinth to remove some parameters such as nitrogen, potassium, phosphorus, total solids, and chloride were also investigated. All experiments were conducted in batch reactors in a greenhouse environment. The leachate samples were collected from Essex–Windsor Regional Landfill, Windsor, Ontario. It was found that this treatment system required the presence of sufficient amount of nutrients (N, P, and K) to ensure plant growth. Optimum growth took place when the initial chloride and sodium concentrations were 560 mg L –1 and 330 mg L –1, respectively. The leachate pH for optimum water hyacinth growth was found to be in the range of 5.8 to 6.0. Total heavy metal concentrations below 0.10 mequiv L –1 supported the plant growth; concentrations above 0.91 mequiv L –1 inhibited the plant growth. Removal efficiencies of nitrogen, potassium, phosphorus, chloride, and total solids from leachate were found to be affected by the growth of water hyacinth. Higher removals were obtained with higher plant growth. Key words : water hyacinth, municipal landfill leachate, chloride, sodium, heavy metals, water hyacinth growth, leachate treatment, bioconcentration factor.